Cross-Cultural Comparison based Syllabus for Cross-Cultural Understanding Class in English Department of Pancasakti University - Prihatin, Yoga; Saleh, Mursid; Rukmini, Dwi; Sofwan, Ahmad (The Journal of Educational Development, 2017)
This study was to design a cross-cultural comparison based syllabus for cross-cultural understanding class in English Department of Pancasakti University. This study used a Research and Development (R&D) model suggested by Borg and Gall (1983) encompassing four phases, exploration, development, field-testing, and dissemination. This study involved 47 third semester students who had attended CCU class in need analysis and 20 students of first semester for the trial. Data was collected by using questionnaire, document analysis, and classroom observation. English Education experts validated the syllabus prototype before trying it out to find out the feasibility and practicality of cross-cultural comparison based syllabus by using a pre-experimental design with one-group Pretest-Posttest design. Pearson Product moment SPSS 22 was used to find out the correlation between pretest and posttest. The try out data was supported by classroom observation rubric and studentsâ feedback. The finding showed that the new developed syllabus was fit to use for cross-cultural understanding class in English Department of Pancasakti University proven by positive correlation and between pretest and posttest; supported by studentsâ good behavior and satisfaction with the new developed syllabus in CCU class.